2022
DOI: 10.1097/jom.0000000000002619
|View full text |Cite
|
Sign up to set email alerts
|

A Moderated Mediation Analysis of New Work-Related Stressors, Psychological Distress, and Absenteeism in Health Care During a Pandemic

Abstract: Objectives: We aimed to evaluate the effects of new work-related stressors on psychological distress and absenteeism and the role of recognition in these relationships. Methods: Moderated path analyses were carried out on a sample of 1128 health care workers. Results: Increased workload related to COVID-19 (coronavirus disease 2019) (β = 1.511, P ≤ 0.01) and fear of COVID-19 (β = 0.844, P ≤ 0.01) were directly associated with a higher level of psychological distress and indirectly (β = 2.306, P ≤ 0.01; and β =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 78 publications
1
7
1
Order By: Relevance
“…Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…, 2017; Bradler et al. , 2016; Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al. , 2002; Kalia and Bhardwaj, 2019; Begum et al.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the coronavirus disease (COVID-19) pandemic has had a significant adverse impact on employees' mental health 30,31 and changed their working style. 32,33 Although many studies have assessed work performance considering various factors related to COVID-19, for example, the new working style, 34 social isolation, 35 and absenteeism, 36 there are few extensive studies. Therefore, comprehensive research will be needed when studying the pandemic's impact on work performance.…”
mentioning
confidence: 99%
“…Regardless, several antecedents of wellbeing are actually linked to HRM practices, emphasizing organizations’ responsibility to ensure that their employees’ wellbeing will not erode. This aspect should not be solely based on an ethical argument but also on an economical one, as, for example, absenteeism may be a consequence of low wellbeing ( Parent-Lamarche and Laforce, 2022 ). This concept highlights the “mutual gains” idea since organizations are unlikely to promote wellbeing on ethical grounds alone ( Guest, 2017 ).…”
Section: Introductionmentioning
confidence: 99%